Effect of Bacillus clausii Capsules in Reducing Adverse Effects Associated with Helicobacter pylori Eradication Therapy: A Randomized, Double-Blind, Controlled Trial - Manuel Plomer (Infectious Diseases and Therapy, 2020)
Abstract Introduction Antibiotic treatment can alter the gut microbiome and cause short-term gastrointestinal adverse effects (AEs). This study assessed the efficacy of lyophilized capsules containing 2 × 109 spores of Bacillus clausii (Enterogermina®; Sanofi Synthelabo) in reducing AEs associated with Helicobacter pylori eradication therapy in Italy. Methods In this randomized, double-blind, single-center, phase IIIB study, 130 adult outpatients with H. pylori infection were assigned to receive one Enterogermina® capsule or placebo three times daily for 2 weeks (1:1). During week 1, all patients received clarithromycin 500 mg, amoxicillin 1 g, and rabeprazole 20 mg twice daily. The primary efficacy outcome was the presence of diarrhea in week 1. Results A total of 130 patients were randomized. The incidence of diarrhea in week 1 was 29% in the B. clausii group and 48% in the placebo group [relative risk (RR) 0.61; 95% confidence interval (CI) 0.39–0.97; p = 0.03]. The incidence of diarrhea remained lower with B. clausii than with placebo in week 2 (RR 0.38; 95% CI 0.14–1.02; p = 0.0422). In week 1, the number of days without diarrhea was significantly higher in the B. clausii group than in the placebo group (6.25 vs. 5.86; p = 0.0304). In both groups, the number of days without diarrhea increased significantly (p < 0.0001) from week 1 to week 2. A total of three AEs occurred in two patients in the placebo group, but none were serious. Conclusions Compared with placebo, Enterogermina® reduced the incidence of, and the number of days with, diarrhea in patients receiving H. pylori eradication therapy. Enterogermina® was well tolerated.